2020
DOI: 10.3390/app10196647
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Mg- or Sr-Containing Bioactive Interfaces to Stimulate Osseointegration of Metallic Implants

Abstract: The purpose of this study resides in the design and deposition of several types of bioactive interfaces with complex composition, targeting a superior osseointegration of bone implants. The experimental approach is framed by two oxide systems, SiO2‒CaO‒P2O5‒ZnO‒MgO and SiO2‒CaO‒P2O5‒ZnO‒SrO, while the percentage values were established as optimised solutions for ensuring wear resistance, bioactivity and beneficial effects on cell metabolism and reproduction. Moreover, two methods dedicated to fils growth (puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The modification of surfaces by the deposition of thin films or their functionalization has become a research direction of great interest, thus contributing to a great extent to the development of fields such as medicine, sensors and different areas of technology. One of the ways to realize this modification is by applying thin films to the surface of different materials [ 98 , 99 ].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The modification of surfaces by the deposition of thin films or their functionalization has become a research direction of great interest, thus contributing to a great extent to the development of fields such as medicine, sensors and different areas of technology. One of the ways to realize this modification is by applying thin films to the surface of different materials [ 98 , 99 ].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…It has been reported that the glass-forming ability (GFA) of the alloys can be improved by the addition of Sr to the Mg-Zn-Ca alloys, [1] and the corrosion resistance of Mg alloys has been improved by the addition of low content Sr [13][14][15]. As a natural component in the human body, strontium (Sr) fully fulfils the requirements of biocompatibility, which can enhance the proliferation of osteoblasts, inhibit osteoporosis, increase bone density and strength, and its degradation products can be metabolised without causing any harm to the human body [13,[16][17][18]. Therefore, the addition of Sr element to Mg-Zn-Ca-Cu alloys may be a feasible approach for improving corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The current challenge is to take a step forward towards reaching improved or even smart devices for medical use by integrating such materials in commercial products. To make this possible, new systems were investigated and unexpected responses were acquired for elements [ 3 ] or compounds [ 4 , 5 ] that were previously declared remarkable for other applications than the biological ones. Thus, a wide range of rare earths were integrated in bioceramics, the results being most of the time appropriate for developing tunable substitutes or personalized therapies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%